2023
DOI: 10.3390/land12051001
|View full text |Cite
|
Sign up to set email alerts
|

In-between Environmental Sustainability and Economic Viability: An Analysis of the State, Regulations, and Future of Italian Forestry Sector

Abstract: Forest management is a complex topic at the interface between sustainability and the resilience of socioeconomic and environmental systems. The influence of market forces, supranational, country and regional policies, as well as climate change, on forest goods and services, is expected to increase in the near future. Such a complex interplay between economic and environmental forces is common to most European countries. The aim of this study is to operationally delineate and discuss the transition of the envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 182 publications
0
1
0
Order By: Relevance
“…This means promoting businesses and management strategies that ensure the resilience of forest ecosystems and the economic vitality of connected supply chains [31]. The forestry sector fulfills multiple functions in Europe, providing socioeconomic benefits that include new jobs and growth opportunities in rural areas, and consolidating, at least indirectly, some recreational functions typical of old-growth woods [32,33]. Extensive research has consistently demonstrated that spending time in forests can effectively reduce stress, improve moods, and even aid in the recovery process from illnesses [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…This means promoting businesses and management strategies that ensure the resilience of forest ecosystems and the economic vitality of connected supply chains [31]. The forestry sector fulfills multiple functions in Europe, providing socioeconomic benefits that include new jobs and growth opportunities in rural areas, and consolidating, at least indirectly, some recreational functions typical of old-growth woods [32,33]. Extensive research has consistently demonstrated that spending time in forests can effectively reduce stress, improve moods, and even aid in the recovery process from illnesses [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%